The Role of ISIS as a Religious Terrorist Group in the Instability of Libya in the Post-Gaddafi Era: The Case of Sirte - Elhudairi, Abdelsalam Mohamed (Religions, 2022)
Stability and security remain the two most important objectives in the post-Gaddafi era since no accord has established a legitimate government in Libya yet. The rivalry of the Tripoli and Tobruk governments has resulted in unabating state insecurity in Libya. This article focuses on the strategic city of Sirte where the insecurity was felt most in the post-Gaddafi era. The significance of this city also comes from its strategic location, which makes it the main target for the political actors that want to control Libya. Deriving from these points, this article analyzes the impact and threat of ISIS as the terrorist group in Sirte.